2015
DOI: 10.4236/health.2015.711155
|View full text |Cite
|
Sign up to set email alerts
|

Family Organization in the Care of Pediatric Heart Transplant Patients: The Genogram as an Investigative Tool

Abstract: This study aimed to describe structure, functionality and development of pediatric heart transplant families, from the understanding of the experienced chronic condition. A descriptive, exploratory study using a qualitative approach was developed in a hospital situated in a city of Northeast Brazil, in 2012. The study was conducted with three families, using the Calgary Family Assessment Model (CFAM). In addition to the genogram, an analysis of the children's/adolescents' family members was conducted at the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The seven risk factors (Life's Simple 7) that people can improve through LS changes, included four health behaviors (stop smoking, eat better, get active, and lose weight) and three health factors (manage blood pressure, control cholesterol, and reduce blood sugar). [58][59][60][61] At present, plenty of relevant studies shown that LS interventions is one of the most important aspects of primary and secondary prevention of CVD's. Elimination of mentioned modifiable risk factors including unhealthy lifestyle allows for prevention of 80% of CVD cases and individuals with desirable lifestyle factors (not smoking, physically active, healthy diet, BMI < 25) are expected to have a 67-72% lower risk of developing heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The seven risk factors (Life's Simple 7) that people can improve through LS changes, included four health behaviors (stop smoking, eat better, get active, and lose weight) and three health factors (manage blood pressure, control cholesterol, and reduce blood sugar). [58][59][60][61] At present, plenty of relevant studies shown that LS interventions is one of the most important aspects of primary and secondary prevention of CVD's. Elimination of mentioned modifiable risk factors including unhealthy lifestyle allows for prevention of 80% of CVD cases and individuals with desirable lifestyle factors (not smoking, physically active, healthy diet, BMI < 25) are expected to have a 67-72% lower risk of developing heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In combination, ecomaps and genograms can offer a holistic overview of relationship dynamics and social support. This makes them suited to investigations of family patterns which cascade through generations – for example, chronic health conditions (Ribeiro et al, 2015), domestic violence (Watts and Shrader, 1998) and property inheritance (Helling and Stovers, 2005). They have also been used to visualise social support in family caregiving (Ray and Street, 2006; 2007; Rempel et al, 2007; Washington, 2009), and to investigate health promotion within social networks (Zanchetta et al, 2007; Rocha et al, 2009; de Oliveira et al, 2010; Correa et al, 2011).…”
Section: Diagrams In Qualitative Research Interviews: Origins Uses Amentioning
confidence: 99%